(untitled) (Kronika Bydgoska, 2017)
The article presents a brief history of establishing and activity in 1961-1975 of the Commission of Propaganda and Tourist Publications WKKFiT in Bydgoszcz. It shows a significant number of publications issued by that organization, dedicated to tourism and sightseeing in the Region of Kuyavia and Pomerania. The Commission also appointed a group of writers consisting of regionalists in various professions, popularizing history, heritage, sightseeing and economic assets of Kuyavia and Pomerania as well as tourist areas comprising the region, the most prominent of which include the Tuchola Forest, the Brodnica Lake District, and the Brda and Wda river basins. Along with the change of the Regional Committee of Physical Culture and Tourism to the Department of Physical Culture in 1975, and later to the Department of Physical Culture and Tourism, the mentioned Committee was disbanded. In addition, the Regional Tourist Information Center, which was subordinate to the Presidium of the Regional National Council, became the Bydgoszcz Division of the Central Tourist Information Center in Warsaw. Despite the formal disbanding of the Commission of Propaganda and Tourist Publications in 1975, writers and reviewers of sightseeing and tourist publications continued to cooperate with the Regional Tourist Information Center, and later with the Bydgoszcz Division of the Central Tourist Information Center, and the Regional Agency for Promotion of Tourism, Limited Liability Company in Bydgoszcz, which tangible effects are the sightseeing publications issued in 1975-1996.